2011
DOI: 10.1007/s10549-011-1351-3
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor therapy: toxicities and management strategies in the treatment of postmenopausal women with hormone-sensitive early breast cancer

Abstract: Aromatase inhibitors (AIs) have been shown to reduce the risk of breast cancer recurrence and are widely used today as adjuvant therapy in women with early stage endocrine-responsive breast cancer. Aromatase inhibitors may be prescribed as initial hormonal therapy, sequentially following 2-3 years of tamoxifen, or as extended adjuvant therapy (following 5 years of tamoxifen). Aromatase inhibitors are generally well tolerated; however, certain side effects, particularly arthralgia/musculoskeletal symptoms and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 99 publications
2
51
3
Order By: Relevance
“…In several studies, AIs use was associated with a higher risk of arthralgia and decreased BMD compared to TAM, and the incidence of discontinuation ranges from approximately 12% to 14% [16] . Effects on cognitive function related to the AIs use have also been reported, similar to the so-called "chemotherapy fog" observed following prolonged cancer CT [71] . However, toxicity is related to individual treatment compliance and depends on the way in which the patient describes and reports the symptoms, and they usually resolve with discontinuation of treatment [16] .…”
Section: Adverse Effectsmentioning
confidence: 64%
“…In several studies, AIs use was associated with a higher risk of arthralgia and decreased BMD compared to TAM, and the incidence of discontinuation ranges from approximately 12% to 14% [16] . Effects on cognitive function related to the AIs use have also been reported, similar to the so-called "chemotherapy fog" observed following prolonged cancer CT [71] . However, toxicity is related to individual treatment compliance and depends on the way in which the patient describes and reports the symptoms, and they usually resolve with discontinuation of treatment [16] .…”
Section: Adverse Effectsmentioning
confidence: 64%
“…Meta-analyses indicate that the vast majority (!90%) of ER þ LN À tamoxifen-treated patients are diseasefree at 5 years, and therefore a decision is required whether to provide extended adjuvant endocrine therapy. Individual patient risk of distant recurrence at 5 years is of clinical importance given the comorbidities associated with endocrine therapies (24) and the recent results from the IDEAL randomized trial of extended endocrine therapy showing high patient noncompliance due to toxicities (25). Results reported herein indicate that BCI low-risk patients assessed at diagnosis continue to have a low probability of distant recurrence after 5 years, and therefore may be recommended to forgo extended therapy, whereas patients with BCI high risk may benefit from extended therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified, with often conflicting results, that factors associated with poor adherence to breast cancer therapy such as type of breast cancer surgery (16,17), severity of side effects (18,19), number of tablets (20)(21)(22), age (11-13, 15, 20, 23, 24), depression and/or the use of antidepressants (24,25), socioeconomic disadvantage (26,27), smoking (28), the impact of breast cancer therapy on quality of life, and the perceived riskbenefit ratio (29).…”
Section: Introductionmentioning
confidence: 99%